Polityka spójności a absorpcja pomocy publicznej z funduszy strukturalnych Unii Europejskiej - Grzeszczyk, Tadeusz A. (Cohesion Policy versus Absorption of State Aid from the European Union Structural Funds, 2006)
The author's research as well as education and consulting experience involve the statement that there exists urgent necessity of intense methodical supply for beneficiaries of state aid from European Union Structural Funds. The methods of evaluation related to the projects being provided with EU Structural Funds subsidies are considered as particularly disdained ones in the field of research, education and consulting in Poland. The author outlines preliminary concept how to broaden the evaluation methods by one more aspect, i.e. application of artificial intelligence.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1099, s. 285-292